Asian Canadian History and the Politics of Historical Knowledge Production - Ishiguro, Laura (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2024)
This introduction outlines the key concerns and contributions of a roundtable on Asian Canadian history. Situating these in the wider context of Asian Canadian studies and Canadian history, it particularly attends to the roundtable’s significance for examining and contesting the silos, approaches, categories, orientations, and narratives that have shaped the place of people of Asian descent in Canadian historiography.